Formal Logical Thought: Proposal of an Instrument for its Evaluation in Subjects of the First Level of Secondary Education (Revista de Psicología, 2023)
The issue of formal thought is addressed, a Piagetian theme that has not lost its validity. The objectives of this work are: (a) To study the psychometric properties of an instrument for the evaluation of formal operative performance elaborated ad hoc from the Longeot (TOFLP) and Flexer and Roberge (FORT) tests; (b) Verify the order of acquisition of the formal operations evaluated in the proposed instrument.A scalographic analysis of the items (Guttman technique) shows that the consistency and reproducibility indices are satisfactory and that the sequence of achievements and level of difficulty of each item conform to Piagetian theory. The validity and consistency of the instrument is tested.
Keywords: formal operations; test; psychometric properties